Risk Factors For Stunting Incidents In Toddlers Aged 6-24 Months : A Case Study In Jeneponto District - Adam, Adriyani; Agus, Rifdah Adilah; Sunarto, Sunarto; Nadimin, Nadimin (Jurnal Kesehatan Manarang, 2024)
Stunting is a problem of growth and development in young children. Stunting in Indonesia is still above the threshold set by WHO, which is 21.6%. The prevalence in South Sulawesi reaches 27.2%, and the district with a high prevalence is Jeneponto Regency, with a percentage of 39.8%. This case-control study aimed to analyze the risk factors for stunting in children aged 6-24 months in Bontomatene Village, Jeneponto Regency, South Sulawesi, Indonesia. The study was conducted from January to February 2024, with a sample of 51 participants (17 cases, 34 controls). Data were collected using a questionnaire and analyzed using the chi-square test. The results showed that maternal height (p=0.006) and low birth weight (p=0.006) were significant risk factors for stunting, while the culture of food taboos was not a risk factor (p=0.333). To address the risk factors, the study recommends ensuring balanced nutrition in the first 1,000 days of life, promoting exclusive breastfeeding, and monitoring the growth and nutritional status of children under five. Additionally, providing education to families with food taboos to encourage a positive attitude towards diverse, nutritious foods is crucial.